Catalytic Abatement of Pollutants from Diesel Exhausts - Pissarello, M.L. (2003)
K and Co,K supported catalysts were studied to determine the mechanism of the soot combustion. The thermal stability of these catalysts and the resistance to water and sulfur are also addressed. The support plays an important role. La2O3 contributes through the formation of carbonate-type intermediates and CeO2 supplies the oxygen necessary for the redox mechanism to take place. However, the addition of Co to the catalyst supported on La2O3, to supply the redox function, leads to a loss of the thermal stability as a consequence of the formation of a perovskite structure. The soot-catalyst contacting phenomenon was also addressed. A synergic La-K effect was observed, by which mechanical mixtures of soot with K-La2O3 showed higher rates than those observed when K and La were deposited on soot. Preliminary experiments using barium as a catalytic trap for NOx and the simultaneous removal of NOx and soot are also presented.